Effects of blowing pinwheel and cough trick on pain in 6-to 12-year-old children during venipuncture: A randomized controlled trial - Merter, Ozlem Selime; Sengul, Zeynep Kisecik; Oguz, Ruveyda (Elsevier Science Inc, 2025)
Purpose: To assess the effects of the blowing pinwheel and cough trick techniques on pain scores in children aged 6 to 12 years during venipuncture. Design: A randomized controlled study. Method: A total of 105 children were allocated into three groups: blowing pinwheel (n: 35), cough trick (n: 35), and a control group (n: 35). Following venipuncture, pain scores were obtained from children's self-reports, parents' reports, and the nurse who carried out the venipuncture, using the Wong-Baker Faces Pain Rating Scale (FACES), Visual Analog Scale (VAS), and Face, Legs, Activity, Cry, Consolability (r-FLACC) scale, respectively. Results: Post-venipuncture pain assessments indicated that children in the blowing pinwheel and cough trick groups experienced significantly lower pain intensity compared with the control group (VAS: p < .001, r-FLACC: p < .001, FACES: p < .001). Analysis of effect sizes revealed that the cough trick group demonstrated a more substantial effect than the blowing pinwheel group. Comparable findings were observed across the VAS, r-FLACC, and FACES pain scales. Conclusions: These findings suggest that distraction techniques, particularly the cough trick, effectively reduce pain perception in children undergoing venipuncture. Practice implications: This study underscores the importance of incorporating distraction techniques, such as blowing pinwheel and the cough trick, into pediatric pain management protocols for venipuncture, thereby improving children's pain experiences. Clinical registration: This study was registered at the U.S. National Library of Medicine Clinical Trials (code: NCT06230601). (c) 2025 Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Venipuncture; Pain; Cough trick; Blowing pinwheel; Children